2022
DOI: 10.1101/2022.04.28.489952
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An essential host dietary fatty acid stimulates TcpH inhibition of TcpP proteolysis enabling virulence gene expression in Vibrio cholerae

Abstract: Vibrio cholerae is a Gram-negative gastrointestinal pathogen responsible for the diarrheal disease cholera. Expression of key virulence factors, cholera toxin and toxin-coregulated pilus, is regulated indirectly by two single-pass membrane-localized transcription regulators (MLTR), ToxR and TcpP, that promote expression of the transcription activator toxT. TcpP abundance and activity are controlled by TcpH, a single-pass transmembrane protein, which protects TcpP from a two-step proteolytic process known as re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 142 publications
0
1
0
Order By: Relevance
“…6E ; see also Files S4 to S6). Prior studies have demonstrated that TcpP, a TTR that positively modulates virulence in Vibrio cholerae , increases its association with detergent-resistant membranes (i.e., liquid-ordered membrane domains) in the presence of ɑ-linolenic acid, a dietary fatty acid ( 57 ). The surface area of the TcpP transmembrane region is 172 Å per amino acid.…”
Section: Resultsmentioning
confidence: 99%
“…6E ; see also Files S4 to S6). Prior studies have demonstrated that TcpP, a TTR that positively modulates virulence in Vibrio cholerae , increases its association with detergent-resistant membranes (i.e., liquid-ordered membrane domains) in the presence of ɑ-linolenic acid, a dietary fatty acid ( 57 ). The surface area of the TcpP transmembrane region is 172 Å per amino acid.…”
Section: Resultsmentioning
confidence: 99%